Edukacja zdrowotna w zakresie HIV/AIDS prowadzona przy pomocy portali społecznościowych = Health education on HIV/AIDS carried out using social networks - Korczyńska, Monika Roberta; Skonieczna, Joanna; Kielan, Aleksandra; Cieślak, Ilona; Olejniczak, Dominik (Journal of Education, Health and Sport, 2016)
Korczyńska Monika Roberta, Skonieczna Joanna, Kielan Aleksandra, Cieślak Ilona, Olejniczak Dominik. Edukacja zdrowotna w zakresie HIV/AIDS prowadzona przy pomocy portali społecznościowych = Health education on HIV/AIDS carried out using social networks. Journal of Education, Health and Sport. 2016;6(2):267-274. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46657 http://ojs.ukw.edu.pl/index.php/johs/article/view/3399 https://pbn.nauka.gov.pl/works/717150 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016. Edukacja zdrowotna w zakresie HIV/AIDS prowadzona przy pomocy portali społecznościowych Health education on HIV/AIDS carried out using social networks Monika Roberta Korczyńska1, Joanna Skonieczna2, Aleksandra Kielan3, Ilona Cieślak3, Dominik Olejniczak2 1 Zakład Epidemiologii, Narodowy Instytut Zdrowia Publicznego – Państwowy Zakład Higieny 2 Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny 3 Studenckie Koło Naukowe Zdrowia Publicznego, sekcja Promocji Zdrowia, Warszawski Uniwersytet Medyczny Słowa kluczowe: edukacja zdrowotna, kampanie prozdrowotne, portale społecznościowe, HIV, AIDS. Key words: health education, health education campaigns, social networks, HIV, AIDS. Streszczenie Pierwsze zalecenia dotyczące profilaktyki HIV/AIDS zostały stworzone przez amerykański Ośrodek Kontroli Chorób (ang. Centers for Disease Control and Prevention, CDC) w 1981 roku [1]. Do dnia dzisiejszego stanowią one fundament działań mających na celu ograniczenie liczby zakażonych, lecz przez ostatnie ponad 30 lat uległy zmianie formy i środki, które można wykorzystywać do osiągnięcia tego celu. Działania profilaktyczne są skuteczne, gdy są dostosowane do ich odbiorcy [2]. Młodzi dorośli (w wieku 20-39 lat) stanowią jedną z grup szczególnie narażonych na wystąpienie nowych zakażeń HIV [3], dlatego w dobie szybko rozwijających się nowych technologii, w szczególności dużego wpływu Internetu i portali społecznościowych na tę grupę wiekową, należy rozważyć skuteczność i efektywność prowadzenia edukacji zdrowotnej w zakresie HIV/AIDS przy użyciu tych środków masowego przekazu. Abstract The first recommendation about HIV/AIDS prevention was created by Centers for Disease Control and Prevention in 1981 [1]. Up to now they provide the foundation of actions aimed at reducing the number of infected people, but during the last 30 years, forms and means which can be used to achieve this goal have changed. Prevention actions are effective when they are adapted to the recipient [2]. Young adults (in age between 20-39 years old) constitute one of the most exposed group to new HIV infections [3], so in the era of rapidly development of new technologies, especially the large impact of the Internet and social networks on this age group, the effectiveness and the efficiency of health education on HIV carried out using this mass media should be considered.